Cop car [videorecording (DVD)] - Bacon, Kevin, 1958-; Whigham, Shea, 1969-; Manheim, Camryn
A pair of ten-year-olds find an abandoned cop car in a field. When they take it for a joyride, it seems like they could kill themselves at any moment. But things only get worse when the small town sheriff goes looking for his missing car. The kids find themselves in the center of a deadly game of cat and mouse they don't understand and the only way out is to go as fast as their cop car will take them.